Infectivity of the DNA from four isolates of JC virus. - Frisque, R J (1979)
The infectivity of JC virus DNA was demonstrated in its most permissive cell culture, primary human fetal glial cells. The amount of infectivity observed in these heterogeneous cultures varied considerably between batches of cells. Contrary to results obtained with the papovaviruses simian virus 40 and BK virus, the calcium technique (F. L. Graham and A. J. van der Eb, Virology 52:456--467, 1973) was found to be more efficient at promoting JC virus DNA infectivity than the DEAE-dextran method (J. H. McCutchan and J. S. Pagano, J. Natl. Cancer Inst. 41:351--357, 1968): maximum infectivity titers of 4 x 10-(4) and 6 x 10(3) fluorescent cell units per microgram of DNA, respectively. These values represent an approximate recovery of infectivity from virus of between 0.02 and 0.14%. Comparisons of infectivity of DNAs obtained from four isolates of JC virus and which differed in their degrees of heterogeneity did not reveal significant differences. The JC virus DNA was not infectious in primary human fetal lung and kidney cells.